Developing and validating a measurement tool to self-report perceived barriers in substance use treatment: the substance use treatment barriers questionnaire (SUTBQ) - Hamid Tavakoli Ghouchani; Hossein Lashkardoost; Hassan Saadati; Seyed Kaveh Hojjat; Faezeh Kaviyani; Kazem Razaghi; Dordane Asghari; Nazanin Gholizadeh (BMC, 2021)
Abstract Background Substance using often cause a wide range of social, health, and psychological problems. This study aimed to develop and validate a questionnaire of barriers of treatment in substance users. Methods In this cross-sectional study, the initial questionnaire was designed based on the evaluation of previous studies. The preliminary tool including 35 Likert-scaled items. After assuring the face validity of the questionnaire, 13 experts' opinions were obtained for assessing or improving the content validity. The reliability was investigated by internal consistency methods using Cronbach's alpha. For measuring the structural validity, the exploratory factor analysis was performed to determine the dimensionality of the questionnaire using principal components extraction and Varimax rotation. Results The preliminary questionnaire consisted of 35 items. After completing the face validity and summarizing the experts' suggestions, 8 items were removed. By calculating the content validity ratio and coefficient, 11 questions were deleted. The internal consistency was calculated to be 0.84 using Cronbach's alpha. In the last stage and according to the results of the factor analysis, three factors fear of or unawareness of treatment, doubt or inefficiency, and social stigma were identified from the 10-items questionnaire, which explained 67.34% of the total variance. Conclusion Considering the necessity of using a validated tool for planning and evaluating effective interventions on people who use substance is inevitable. The Substance use Treatment Barriers Questionnaire is designed with 10 items and 3 dimensions, which has appropriate validity and reliability and can be used to determine the obstacles for treatment or factors that lead to discontinuing treatment.